Production and mechanistic evalution of the stability of polymorphic olanzapine in solid dosage forms - Paisana, Maria de Castro (2016)
Tese de doutoramento, Farmácia (Tecnologia Farmacêutica), Universidade de Lisboa, Faculdade de Farmácia, 2016